National food & agriculture policy (2002-2020) (The Ministry [Belmopan]BZ, 2003)
Provides the global framework for action of the productive sector. Reviews policies and looks at challenges and constraints facing the sector. Presents policies for agriculture, fisheries, cooperatives and support mechanisms/services.
Keywords: FOOD POLICY